Sistema de costos por procesos para el centro de acopio Sierra Nevada, ubicado en la comuna Cumbijín, perteneciente al cantón Salcedo en el período Enero-Junio 2019. - Naula Salazar, Jimena Paola (2020)
The Sierra Nevada Collection Center, through its activity, supports the small producers of the Salcedo canton, Cumbijín commune, by acquiring the total of their production under specified conditions that create a mutual commitment. The objective of this work was to design a system of costs by processes, to properly establish unit and total production cost system, and to establish the profit margin in a clear and precise manner. It began with the prior analysis of the identified problem and its respective justification, aspects that led to the definition of the study objectives. This information was used to support this work with theoretical data and definitions related to the concepts of process costs in production. Inductive, deductive and analytical methods were used. The research was descriptive, and its design was field and documentary. Based on the information gathered, a system of process costs was designed, adapted to the needs and particular characteristics of the economic activity developed by the company. The conclusions reveal the reality of the current problem and the recommendations are aimed at eliminating them.